Deaths among Women of Reproductive Age: an Explorative Case Study among Abortion Seekers - Gautam, Preeti; Puri, Mahesh C.; Karki, Sunita; Foster , Diana Greene (Journal of Nepal Health Research Council, 2024)
In Nepal, abortion was legalized in 2002. Yet many women are denied abortion services. Women denied abortion services may either continue their pregnancies or find abortion care elsewhere. However, what is not known is the consequences on women, and their children after accessing abortion services or after being denied abortion services. This comment aims to understand the cause of death of women who sought abortion services between 2019 and 2020 and were enrolled in a longitudinal nationwide study of the consequences of legal abortion access in Nepal. Women were interviewed 6 weeks and every 6 months for 3 years after seeking abortion. During the follow-up interviews, the field research assistants were informed about the death of the clients. Once the death was reported, a trained senior research staff visited the deceased persons house and interviewed family members including husbands, maternal parents or in-laws to explore the cause of death. A total of nine deaths were reported between April 2019 and December 2022. Out of nine deceased women, four received abortions while five of them were initially denial abortion services. The majority of the deaths were due to suicide followed by tuberculosis. None of the deaths were caused by abortion or birth.Keywords: Death; Nepal; reproductive ages; womens health.